Chiral Co(iii)–salen complex supported over highly ordered functionalized mesoporous silica for enantioselective aminolysis of racemic epoxides. Issue 111 (16th November 2016) - Islam, Md. Mominul; Bhanja, Piyali; Halder, Mita; Kundu, Sudipta K.; Bhaumik, Asim; Islam, Sk. Manirul
Abstract : New mesoporous chiral Co(iii )-catalyst has been synthesed and used in the synthesis of chiral β-amino alcohols with excellent yield and enantioselectivity (ee > 99%) under neat conditions at RT. Abstract : Here we demonstrate the synthesis of a novel chiral Co(iii )–salen complex supported functionalized 2D-hexagonal mesoporous silica material Co(iii )@AFS-1. This material has shown excellent catalytic activity for the regio- and enantioselective asymmetric ring opening (ARO) of terminal and meso epoxides using various aromatic as well as cyclic amines to produce chiral β-amino alcohols having very good enantioselectivities (ee > 99%) at ambient temperature under solvent-free neat conditions.